Analytical Chemistry Methods of Estimating the Hydraulic Lime Characteristics of Mortars from a Spanish Colonial Period Fortification in the Philippines: Perspective of a Southeast Asian Country | Mga Pamamaraan ng Suriing Kapnayan sa Pagtantya ng Katangiang Haydroliko ng Apog sa Argamasa na Mula sa Isang Panahon ng Kastilang Kuta sa Pilipinas: Pananaw ng Isang Bansa sa Timog-Silangang Asya - Jan-Michael Cayme (SPAFA Journal, 2022)
This study has provided an analytical chemistry method to reveal the production technologies employed in lime mortar making from a Spanish Colonial Period fortification in Bacolod, Lanao del Norte, Philippines. Analytical techniques such as Energy Dispersive X-ray Fluorescence (EDXRF) and Thermogravimetric analysis (TGA) effectively provided general information on the chemical composition of the lime mortars and the hydraulic nature of the binder used. Mortar samples from different areas in the fort, were found to be made from a calcitic lime source possibly of marine shell origin. The hydraulic characteristic of both mortars is due to clay additives suggesting that local knowledge of this process is known during that period. The EDXRF and TGA techniques applied to the samples in this study will address the lack of systematic and detailed baseline chemical data on historical lime mortars in the Philippines and other Southeast Asian countries, which is vital for future conservation work in the ASEAN region.